Principal Management in Improving School Achievement at SMP Darul Hikam Bandung - Yudianto, Yudianto; Rukman, Entang; Hanafiah, Hanafiah; Karim Fatkhullah, Faiz (The International Journal of Education Management and Sociology, 2023)
Principal Management in Improving School Achievement at SMP Darul Hikam Bandung. The purpose of this study is to get an overview of school principal management in terms of planning, organizing, implementing and supervising. Research Methods with a qualitative approach that focuses on in-depth observation. Therefore, the use of qualitative methods in research can produce a comprehensive study of phenomena to be applied in school achievement. Data collection techniques through interviews, observation and documentation studies. The results of the research in terms of planning school programs are carried out jointly with representatives and teachers. In practice, it has shown that there is a large increase in the application of good principal management to increasing school achievement. Supervision and evaluation have been carried out by the school principal as an improvement to the program of activities in increasing the next school's performance.